Enhancing Student Engagement and Reading Comprehension of Twice-Exceptional Students with ADHD through Picture Books and Differentiated Instruction: A Classroom Action Research - Ruth Stivenny Queen Renti; Tini Mogea; Nihta V. F. Liando (Austronesian: Journal of Language Science & Literature, 2026)
This study investigated the use of digital picture books supported by differentiated instruction to enhance student engagement and vocabulary-based reading comprehension in a Grade 1–2 inclusive English classroom. The study focused on twice-exceptional (2e) students with Attention Deficit Hyperactivity Disorder (ADHD) characteristics who experienced difficulties maintaining attention and understanding vocabulary during reading activities. This study employed Classroom Action Research (CAR). The participants were five students in a mixed Grade 1–2 inclusive classroom at SD Sinar Kasih Tomohon. Data were collected through a student engagement observation sheet and a vocabulary-based reading comprehension test. The findings showed improvements in both student engagement and vocabulary-based reading comprehension. The mean student engagement score increased from 2.04 in Cycle 1 to 2.84 in Cycle 2, indicating a higher level of participation, attention, and involvement in classroom activities. Students’ vocabulary-based reading comprehension also improved from 55% in Cycle 1 to 84% in Cycle 2. These improvements suggest that digital picture books provided meaningful visual support for vocabulary learning, while differentiated instruction helped address students’ diverse learning needs and encouraged active participation. The study concludes that the use of digital picture books supported by differentiated instruction can enhance student engagement and vocabulary-based reading comprehension among twice-exceptional (2e) students with ADHD characteristics in an inclusive English classroom. The study suggests that inclusive classrooms effectively support twice-exceptional (2e) students through differentiated instruction, visual materials, and individualized scaffolding, emphasizing responsive teaching rather than curriculum modification alone.